2001
DOI: 10.1016/s0925-4773(01)00520-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of two zebrafish genes, cxcr4a and cxcr4b

Abstract: We cloned and mapped two novel zebrafish genes, cxcr4a and cxcr4b, which are closely related to mammalian CXCR4. Expression analysis by reverse transcription-polymerase chain reaction and in situ hybridization demonstrated that these two genes are expressed in most cell lineages known to express Cxcr4 in mammals. These genes are co-expressed in lateral mesoderm and posterior midbrain. The transcripts of cxcr4a were detected in interneurons and endoderm, whereas cxcr4b was specifically expressed in sensory neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 8 publications
5
108
0
Order By: Relevance
“…Finally, we observed that the sox3-expressing p4 subdomain migrates posteriorly from its original domain along the body axis after the 20-somite stage (data not shown). Given that this migration trend of the p4 subdomain is similar to that of the posterior lateral line primordium, as revealed by morphological observation (Laguerre et al, 2005) and expression of the chemokine receptor cxcr4 (Chong et al, 2001;David et al, 2002), we suggest that the p4 subdomain represents the anlage of the posterior lateral line system.…”
Section: Early Development Of the Epibranchial Placode In Zebrafishsupporting
confidence: 56%
“…Finally, we observed that the sox3-expressing p4 subdomain migrates posteriorly from its original domain along the body axis after the 20-somite stage (data not shown). Given that this migration trend of the p4 subdomain is similar to that of the posterior lateral line primordium, as revealed by morphological observation (Laguerre et al, 2005) and expression of the chemokine receptor cxcr4 (Chong et al, 2001;David et al, 2002), we suggest that the p4 subdomain represents the anlage of the posterior lateral line system.…”
Section: Early Development Of the Epibranchial Placode In Zebrafishsupporting
confidence: 56%
“…Regardless of the precise nature and extent of the differences between both teleost IL-11 genes, apparently, there has been an evolutionary advantage to the possession of duplicate IL-11 genes in fish. As IL-11 is a pleiotropic cytokine, it is possible that the many functions it fulfills in mammals have been divided between two genes in bony fish, as has been suggested for other duplicate genes in fish (Chong et al 2001;Huising et al 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…Cxcr4b is a chemokine receptor of the G-Protein Coupled Receptor (GPCR) gene family (Chong et al, 2001(Chong et al, , 2007). These receptors play an important role in defining directionality of cell migration of germ cells, lateral line, and somites during embryogenesis (Doitsidou et al, 2002;Gilmour et al, 2004;Hollway et al, 2007).…”
Section: Diffusion Coefficient Measurements In Live Zebrafish Embryosmentioning
confidence: 99%
“…A stop codon was removed from Cxcr4b gene previously cloned in a pPCR-Script vector (Stratagene, CA) (Chong et al, 2001). The Cxcr4b gene was digested out using SacII and XhoI and then subcloned into pEGFP-N1 (Clontech) vector digested with the same enzymes.…”
Section: Plasmidsmentioning
confidence: 99%